Classificação morfológico, critérios de malignidade, expressão gênica de C-MYC e imunoistoquímica de C-MYC, p53, p21 e p27 no tumor venéreo transmissível canino - Lima, Caroline Rocha de Oliveira (2013)
The present concept about carcinogenesis is that normal cells are transformed into tumor by mutations that activate oncogenes, inhibit tumor suppressor genes or trigger genetic instability. However, studies suggest that some neoplastic types can behave like infectious agents and be transmitted from one host to another, similar to what occurs with the canine transmissible venereal tumor (TVT). The TVT histogenesis is not fully known, because the studies are controversial and do not bring about the results elucidating cell line that characterized the neoplasm. However, research continues in order to elucidate this question and identify the ancestral genetic TVT. Recently, a cytomorphological classification was proposed for the TVT, including plasmacytoid types, linfocitoide and mixed. Nevertheless, many features of the development and behavior of this dogs transmissible neoplasm are still poorly understood. Accordingly, we evaluated the different morphological patterns of the tumor, the macroscopic aspects, the criteria of malignancy, the molecular identification of the tumor, by inserting the element LINE-1 in the C-MYC gene, the immunohistochemical expression of the C-MYC, p53, p21 and p27, and the relationship between the proteins C-MYC, p53, p21 and p27, the block of the cell cycle and apoptosis of tumor cells. The results indicate that the cytological examination allows better characterization of patterns and cytomorphologic criteria of malignancy of TVT compared to histological examination, which can identify the types plasmacytoid, linfocitoide and mixed. It was further observed that the TVT presents morphological peculiarities that may interfere with tumor behavior and response to chemotherapy, especially those related to more aggressive and have been observed in plasmacytoid TVT, cytomorphological most common type of this tumor. The identification of molecular rearrangement LINE-1/C-MYC features specific molecular changes for TVT that may be introduced as supplementary diagnostic method of cancer, especially in highly undifferentiated tumors. Immunohistochemical analysis and the relationship between C-MYC, p53, p21 and p27 revealed functional abnormalities in these proteins, interfering with biological events in cell cycle control and apoptosis, and may thus contribute to the genesis and neoplastic progression.